Public awareness, attitudes, behavior and norms building green hospitals' power - Ari Nurfikri; Deni Danial Kesa; Mingchang Wu; Elsa Roselina; Abas Hidayat (Heliyon)
Hospitals function to provide health services to the community, but they have the potential to be contributors to hazardous waste, climate change, and global warming. The concept of green hospitals is now necessary for changing hospital functions developed by various hospitals worldwide. The success of the green hospital concept requires support from the perspective of the surrounding society. The research aims to analyze public awareness, attitudes, behavior, and norms to build the power of green hospitals. This research method is simple linear regression. The research instrument used a questionnaire. The respondents of this research were 400 green hospital users from Indonesia and Taiwan. The data analysis method includes tests for normality, linearity, and heteroscedasticity. Once these three tests are met, a linear regression analysis is conducted to understand the influence and prediction of public awareness, attitudes, behavior, and norms on building the power of green hospitals. The research results show that each aspect of public awareness, attitudes, behavior, and norms significantly positively influence the building of the power of green hospitals. Each additional value of public awareness, attitudes, behavior, and norms is expected to strengthen the image of a green hospital. Maintaining the sustainability of green hospital programs worldwide not only focuses on implementing the green concept but also needs to pay attention to public perception when choosing a hospital. The research contribution is significant to developing more sustainable green hospitals, increasing knowledge about green hospitals, and increasing public interest and perception of green hospitals.